Influência do exercício físico sobre parâmetros de dependência e recaída em ratos expostos à anfetamina: aspectos comportamentais e bioquímicos - Segat, Hecson Jesser (2015)
Amphetamine compounds and its derivatives are widely used in clinical medicine, but it is known that frames can cause dependence, tolerance and withdrawal. Furthermore, these drugs can alter metabolism and the functions of central neurotransmitters causing oxidative imbalances. In this sense it is already documented that exercise improves the conditions of well-being and self-esteem, and improve the plasticity and thus neuronal protection. In this context, the present study aimed to evaluate the influence of regular and continuous exercise on anxiety and behavioral parameters related to relapse to the use of amphetamine in an animal model of conditioned place preference (CPP). Male Wistar rats were conditioned to the use of AMPH or vehicle for 14 days and then half of each group was subjected to aerobic, regular and continuous physical activity for 5 weeks, while the others were not exercised. At the end of the last exercise session, the animals were re-conditioned to the use of AMPH/vehicle for more 3 days. After this phase, the animals were subjected to behavioral testing CPP to evaluate relapse to drug use, and the elevated plus maze to measure anxiety parameters. Hippocampal oxidative status was evaluated by levels of generation of reactive species (RS), carbonyl protein (CP), and activity levels of catalase (CAT) and Na+K+-ATPase, respectively. It was observed that the per amphetamine was able to develop is the CPP in the animals, however after the completion of 5 weeks of aerobic exercise, there was a reduction in the rate preferably compared to sedentary rats indicating a lower rate of relapse to amphetamine. In addition, exercise was shown to be beneficial to reduce the degree of anxiety and oxidative damage in these animals by amphetamine. Thus, regular and continuous exercise is a promising tool in the treatment of dependence and relapse to the indiscriminate use of drugs.